Fatigue damage monitoring of structural aluminum alloys - Ігнатович, С.Р.; Карускевич, М.В.; Карускевич, О.М.; Хижняк, С.В.; Якушенко, С.А. (Proceedings of National Aviation University (archive), 2012)
Results of the experiments directed on creation of a new tool method of fatigue damage diagnostics and an estimation of a residual life of aviation designs are presented. It is shown, that the defo rmation relief formed on a surface of cladding layer of sheets of constructional alloys Д-16АТ, 2024-Т3, 7075-Т6 can be considered as the metal damage indicator under cyclically repeating loadings.